Attachment of Treponema pallidum to fibronectin, laminin, collagen IV, and collagen I, and blockage of attachment by immune rabbit IgG. Issue 6 (December 1984) - Fitzgerald, T J; Repesh, L A; Blanco, D R; Miller, J N
Abstract : As shown by scanning electron and phase contrast microscopy, Treponema pallidum attached in vitro to basement membranes purified from kidney cortex tissues or from retinal vessels. This organism also attached to the extracellular matrix remaining after cultured cells had been solubilised with Triton X. Fibronectin, laminin, collagen, IV, collagen I, and hyaluronic acid are structural components of basement membranes and extracellular matrices. Experiments were performed to investigate the in vitro attachment of T pallidum to each of these components. Viable or heat inactivated treponemes were added to glass coverslips precoated with different concentrations of each component. After various times of incubation, coverslips were washed and the attached organisms were counted. Large numbers of viable organisms attached to each of these five components. In contrast, heat inactivation sharply reduced numbers of attached organisms. The IgG fractions of immune and non-immune rabbit serum samples were affinity purified using protein A. T pallidum was preincubated with both fractions, then incubated with either intact cultured cells or with coverslips coated with the five tissue components. The IgG from immune serum blocked treponemal attachment to the cultured cells and to fibronectin, laminin, collagen IV, and collagen I, but not to hyaluronic acid. These results are discussed in terms of attachment mechanisms of T pallidum and potential applications to in vivo infection.